Specialized flower visitation in montane butterflies is associated with positive population trajectories over time - Tara Christensen; Christopher A. Halsch; Lee A. Dyer; Angela M. Smilanich; Arthur M. Shapiro; Matthew L. Forister (Ecology, 2025)
Insect biodiversity is under threat from multiple stressors, including climate change and extreme weather. For butterflies, nectar resource use is an understudied trait in relation to population trajectories and responses to global change. Here, we characterize nectar breadth for 50 species of montane butterflies occurring in the Sierra Nevada mountains of California and Nevada. These species displayed a wide spectrum of nectar use, including relative specialists and extreme generalists. Further, we examined how nectar breadth and other species traits, including latent variables indicating ecological flexibility and dispersal potential, were indicative of long‐term population trajectories and responses to an extreme drought event from 2011 to 2015. Species that were more nectar‐generalized were more likely to be declining, but nectar breadth did not predict how a species responded to extreme drought. Greater ecological flexibility, as reflected in other traits, was positively associated with population performance, while dispersal potential was negatively associated with population trajectories. Drought response was strongly associated with flight period, where species that fly later in the season are more susceptible to the negative effects of drought. Our study highlights the importance of considering butterfly nectar breadth in predicting population resilience and challenges assumptions about dietary generalism as a buffer against environmental change.